Weighing the future : race, science, and pregnancy trials in the postgenomic era - Valdez, Natali, 1986- (Critical environments (Oakland, Calif.), 2022)
"Epigenetics is the study of heritable changes in gene expression and has been heralded as one of the most promising new fields of scientific inquiry. Current large-scale pregnancy studies draw on epigenetics to connect pregnant women's behavioral choices, like diet and exercise, to future health risks for unborn babies. As the first ethnography of its kind, Weighing the Future examines the sociopolitical implications of ongoing pregnancy trials in the United States and the United Kingdom, illuminating how processes of scientific knowledge production are linked to capitalism, surveillance, and environmental reproduction. The environments we imagine to shape our genes, bodies, and future health are tied to race, gender, and structures of inequality. This groundbreaking book makes the case that science, and how we translate it, is a reproductive project that requires feminist vigilance. Instead of fixating on a future at risk, this book brings attention to the present at stake"--